Characterisation and comparison of immune response mechanisms in an indigenous and a commercial pig breed after classical swine fever vaccination. (2nd November 2021) - Mehrotra, A.; Bhushan, B.; Kumar, A.; Panigrahi, M.; Chauhan, A.; Kumari, S.; Saini, B. L.; Dutt, T.; Mishra, B. P.
Summary: The live attenuated classical swine fever (CSF) vaccine has been successfully used to prevent and control CSF outbreaks for 6 decades. However, the immune response mechanisms against the vaccine remain poorly understood. Moreover, very few reports exist regarding the breed differences in the response to CSF vaccine. In this study, we generated the peripheral blood mononuclear cell transcriptomes of indigenous Ghurrah and commercial Landrace pig breeds, before and 7 days after CSF vaccination. Subsequently, between and within‐breed differential gene expression analyses were carried out. Results revealed large differences in pre‐vaccination peripheral blood mononuclear cell transcriptome profiles of the two breeds, which were homogenised 7 days after vaccination. Before vaccination, gene set enrichment analysis showed that pathways related to antigen sensing and innate immune response were enriched in Ghurrah, while pathways related to adaptive immunity were enriched in Landrace. Ghurrah exhibited greater immunomodulation compared to Landrace following the vaccination. In Ghurrah, cell‐cycle processes and T‐cell response pathways were upregulated after vaccination. However, no pathways were upregulated in Landrace after vaccination. Pathways related to inflammation were downregulated in both the breeds after vaccination. Key regulators of inflammation such as IL1A, IL1B, NFKBIA and TNF genes were strongly downregulated in both the breeds after vaccination. Overall, our results have elucidated the mechanisms of host immune response against CSF vaccination in two distinct breeds and revealed common key genes instrumental in the global immune response to the vaccine.